Appendicitis and cholecystitis during the COVID-19 outbreak: a multicentre experience (Swiss Medical Weekly, 2021)
BACKGROUND: The aim of this study was to assess diagnosis severity, perioperative management and outcomes of two common urgent general surgery situations, appendicitis and cholecystitis, during the COVID-19 outbreak in a region with a high incidence of COVID.METHODS: Retrospective analysis of all appendicitis and cholecystitis cases in a region of western Switzerland (population 850,000) during the first pandemic peak. Primary endpoints were delay after first symptoms to consultation and delay to surgery. Secondary endpoints were disease severity and postoperative outcome compared with the same period in 2019.RESULTS: 214 patients were included: 99 during the 2020 pandemic and 115 in 2019. Median time to consultation for appendicitis was 48 hours (interquartile range [IQR] 24–96) in 2020 and 24 hours (12–36) in 2019 (p = 0.004); for cholecystitis, it was 48 hours (24–96) in 2020 and 36 hours (24–72) in 2019 (p = 0.28). Median time to surgery after consultation for appendicitis was 6.5 hours (IQR 4–18) in 2020 and 7.3 hours (5–9) in 2019 (p = 0.68), for cholecystitis 20 hours (12–48) in 2020 and 23 hours (14–39) in 2019 (p = 0.91). More antibiotics were prescribed after appendectomy in 2020 (46 vs 31%, p = 0.026). Significantly more perforations/abscesses related to appendicitis and cholecystitis were observed in 2020 during the COVID-19 outbreak (p = 0.007 and p = 0.044, respectively). No differences were found for postoperative complications and length of stay.CONCLUSIONS: A delay in patients’ arrival at the emergency room was observed for appendicitis. No delay to surgery during the pandemic was observed. A higher rate of perforations and abscesses associated with appendicitis and cholecystitis was observed during the pandemic period. Morbidity and reoperation rate did not change.